2021
DOI: 10.1002/nau.24776
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron has longer treatment persistence than antimuscarinics: Real‐world data from a Korean national cohort database

Abstract: Aims: To descriptively evaluate treatment persistence among adults who received mirabegron or antimuscarinics in South Korea. Methods: This study involved a retrospective analysis of the Health Insurance Review and Assessment (HIRA) database. Patients (≥18 years) who had a new prescription for an overactive bladder (OAB) target medication (mirabegron/ antimuscarinic) within an 8-month index period (July 1, 2015-February 29, 2016) were included. The date when the target (index) medication was dispensed was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In previous 15 clinical studies, Mirabegron, Solifenacin, and Fesoterodine were associated with the highest persistence rates. However, a real‐world data set from South Korea 21 demonstrated the persistence rate at 1 year to be 13.5% for Mirabegron and 4.9% for all antimuscarinics. Multicriteria Decision Analysis 22 Applied to the Clinical Use of Pharmacotherapy found Solifenacin 5 mg in combination with Mirabegron 50 mg is the best compromise between the higher benefits but lower safety of Fesoterodine 4 or 8 mg, or the safer but lesser benefits of Mirabegron 25 mg. We found high claims of Fesoterodine indeed but also high claims of Trospium.…”
Section: Discussionmentioning
confidence: 99%
“…In previous 15 clinical studies, Mirabegron, Solifenacin, and Fesoterodine were associated with the highest persistence rates. However, a real‐world data set from South Korea 21 demonstrated the persistence rate at 1 year to be 13.5% for Mirabegron and 4.9% for all antimuscarinics. Multicriteria Decision Analysis 22 Applied to the Clinical Use of Pharmacotherapy found Solifenacin 5 mg in combination with Mirabegron 50 mg is the best compromise between the higher benefits but lower safety of Fesoterodine 4 or 8 mg, or the safer but lesser benefits of Mirabegron 25 mg. We found high claims of Fesoterodine indeed but also high claims of Trospium.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with other previous persistence investigations, which have typically found that older and treatment-experienced patients persist with OAB medication for a longer period of time than younger and treatment-naïve patients [ 8 , 10 , 21 23 ]. Furthermore, some studies that have also been conducted in East Asia have found that male patients persist with treatment longer than female patients [ 10 , 22 ]. Older and treatment-experienced patients may be willing to persist with treatment as they may have experienced the condition for a longer duration and might be more familiar with the benefit–risk profile of OAB therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Int Neurourol J June 30, 2023 isfaction with the treatment was assessed with the Patient Global Impression (PGI) scale at week 12. The level of satisfaction was based on a 7-point scale; very much improved (1), much improved (2), minimally improved (3), no change (4), minimally worse (5), much worse (6), and very much worse (7). A PGI ≤3 was defined as 'effective improvement' and a PGI ≤2 was defined as 'significant improvement. '…”
Section: Injmentioning
confidence: 99%
“…Mirabegron, the first U.S. Food and Drug Administration (FDA)-approved β3 agonist for treating OAB, has been the only available drug for patient's intolerant to anticholinergics. Compliance to mirabegron is reported to be higher than that of anticholinergics due to different in possible side effects and their intensity [6,7]. In addition, combination therapy with various anticholinergics has expanded possible treatment options.…”
Section: Introductionmentioning
confidence: 99%